Menjaga konektifitas Internet Agar Selalu Up Dengan Metode Fail Over Berbasis Mikrotik Pada SMA Darusallam Jakarta - Toni Sukendar; Mohammad Ikhsan Saputro (Universitas Bina Sarana Informatika, 2017)
Along with the increasing need for Internet usage in the computer network has resulted in the development of network technology itself. The availability of resources that is inversely proportional to the current level of demand has demanded network technology to float a new technique that can address the problem. Load balancing is one of the routing techniques that can utilize multiple Internet resources to be used simultaneously or interchangeably. However, there are various methods that can be used, including the method of NTH, PCC (Per Connection Classifier) and Fail Over. This study discusses load balancing with Fail Over method in maintaining Internet connectivity from Lost Conection interference